A Qualitative Investigation of Sociocultural Factors Impacting Assessment Design in Multilingual Education - Behdarvand, Zeinab (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the sociocultural factors that influence assessment design in multilingual educational settings, with a focus on secondary schools in Tehran, Iran. The study employed a qualitative design using semi-structured interviews to capture the lived experiences and perspectives of educators, curriculum designers, and education policymakers engaged in multilingual classrooms. A total of 22 participants were selected through purposive sampling, and data collection continued until theoretical saturation was achieved. All interviews were conducted in Persian, transcribed verbatim, and analyzed using thematic analysis with the support of NVivo software. The data analysis process followed Braun and Clarke’s six-phase framework, allowing for both inductive and deductive theme development rooted in sociocultural theory. Three main themes emerged from the analysis: (1) Cultural Contextualization in Assessment, encompassing subthemes such as local norms, religious values, and indigenous knowledge; (2) Linguistic Diversity and Assessment Equity, addressing issues like language accessibility, multilingual strategies, and test anxiety among non-dominant language speakers; and (3) Institutional and Policy Constraints, highlighting standardization pressures, lack of multilingual policy guidelines, and limited teacher autonomy. Participants described how cultural misalignment, language barriers, and bureaucratic rigidity compromise the validity, fairness, and inclusiveness of assessments. Teachers employed informal strategies to adapt assessments, but these were often unsupported at the institutional level. The study demonstrates that sociocultural factors critically shape assessment practices in multilingual classrooms. Culturally and linguistically responsive assessment design requires systemic reforms, including policy support, professional development, and increased flexibility for educators. These changes are essential for ensuring equitable educational outcomes in linguistically diverse contexts.